Economic Support for Individuals During the First Wave of COVID-19 : The Australian Experience - Hodgson, Helen (2021)
The Australian response to the COVID pandemic was on two fronts: the public health response was to keep the virus out of Australia, using border closures and social distancing measures as the first line of defence; and the economic response was through fiscal measures to support businesses and individuals who were affected by the disruption of these measures. The measures to support individuals who lost income as a result of the economic disruption included income support; rent moratoria; and access to superannuation. Further fiscal stimulus measures were introduced in subsequent budgets. These policies provided essential support during the pandemic in 2020. The economy recovered faster than expected following that first wave, resulting in some unintended outcomes in the labour market, the housing market and superannuation. These are likely to widen income and wealth gaps in Australia. These economic supports had been withdrawn by the time of the outbreak of the Delta variant on the east coast of Australia in mid-2021. The replacement programs provide less support than their predecessors, and the economy is showing the effects, particularly on income insecure residents. As the economy stabilises, the Government must adopt policies that protect the vulnerable, not revert to austerity settings.